Vibration fault signal analysis and diagnosis of flue gas turbine. (April 2022) - Xiong, Huiying; Peng, Yiheng; Hu, Yiyang; Zhang, Lin; Li, Ying
Highlights: The geometric model and mathematical model of flue gas turbine rotor are established, and the fault mechanism is studied. Through on-line monitoring of vibration signal of flue gas turbine rotor, the running state of flue gas turbine is comprehensively analyzed. It provides an important reference for condition monitoring and fault diagnosis of flue gas turbine. Abstract: Flue gas turbine is a kind of typical rotating machinery. It uses the flue gas expansion which contains a lot of heat energy and pressure energy generated in the catalytic cracking process to drive the axial-flow compressor or generator to rotate. Due to the complex structure, bad operating environment, poor stability, and large vibration of the flue gas turbine, its failure rate is high, which causes immeasurable economic losses and safety hazards. Therefore, how to effectively obtain, extract and identify the fault information of flue gas turbine is a difficult problem in the field of fault diagnosis technology. In this paper, aiming at two kinds of faults in the tp9-90 flue gas turbine system, i.e., rotor misalignment and unbalance causing excessive vibration, the corresponding geometric model and mathematical model are established, and the fault mechanism is revealed. Through on-line monitoring of flue gas turbine rotor vibration signal, the running state of flue gas turbine is comprehensively analyzed, and the technological transformation is carried out according to the fault causes, the improved flue gas machine runs smoothly, and the vibration and failure rate are obviously reduced. This study provides an important reference for condition monitoring and fault diagnosis of flue gas turbines.